2015
DOI: 10.1186/s12957-015-0434-8
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic closure of gastric tube perforations with titanium clips: a four-case report

Abstract: Perforation of a gastric tube is a rare yet lethal complication after esophagectomy for esophageal cancer treatment. Currently, over-the-scope clip (OTSC) is an effective way to treat gastric tube perforation. Due to the lack of OTSCs, we invented an alternative method composed of a titanium clip and gastroscope. The aim of this study was to describe this novel endoscopic device in the treatment of gastric tube perforation. We used a titanium clip system to treat 4 male patients (range, 53 to 77 years with gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A large number of clinical trials have shown that, the use of vascular clips as a means of hemostasis in gastric and colorectal polypectomy can effectively prevent postoperative bleeding and digestive tract perforation [12][13][14][15][16][17].…”
Section: Yoshida Et Al Studied the Application Of Mg-mentioning
confidence: 99%
“…A large number of clinical trials have shown that, the use of vascular clips as a means of hemostasis in gastric and colorectal polypectomy can effectively prevent postoperative bleeding and digestive tract perforation [12][13][14][15][16][17].…”
Section: Yoshida Et Al Studied the Application Of Mg-mentioning
confidence: 99%
“…Fast-hardening amino acid solution [8] Fibrin glue [6,9] Self-expanding stent [5,10] Dual self-expandable stent [11] Placement of a cardial septal occluder [12] Titanium clips [13]…”
Section: Endoscopic Obliterationmentioning
confidence: 99%